A Fuzzy Rule-Based Fog Cloud Computing untuk Menganalisis Faktor Penyebab Kematian Ibu Meninggal Masa Postpartum - Arif Wicaksono Septyanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Analysis of the causes of post-partum maternal death is very important in reducing maternal mortality. The post-partum maternal mortality rate in Indonesia is very high, around 359 in 100,000 births. The factors of post-partum maternal mortality are rarely analyzed more deeply so that there is no sustainable treatment. In this study, the authors used a fuzzy rule-based fog cloud computing system to monitor maternal mortality based on vital signs and physical signs using 10 parameters of the causes of postpartum maternal death. Fog cloud is used for data processing on a local server in order to reduce the burden when using cloud computing. The initial analysis of maternal mortality parameters was changed to low, medium and high ranges and then monitored on seven days post-partum. From the results of the analysis, it was found that the dominant factor of post-partum maternal mortality for vital signs was influenced by Blood Pressure with an MF value of 0.44 with status